Local Economic Development and Tourism - Hayakawa, Tatsuji; Rivero, Monica (World Bank, Washington, DC, 2012)
The World Bank dropped its engagement in the tourism sector during the 1980s after twenty years of financing tourism projects which included infrastructure for resort sites, lines of credit for hotels, training, and investment in hotels and other tourism related projects. At the time, World Bank lending for tourism in Latin America and the Caribbean (LAC) was just US$350 million per year. After the tourism department closed in the late 70s, some projects supporting tourism continued, but total annual lending for tourism fell to US$150 million by the mid-80s. It had reached a low of US$50 million by the mid-90s. To the mid-90s the trend started reversing itself and by 2007 annual lending for tourism grew to US$175 million, and is expected to pass the $550 million dollar mark during FY09. The World Bank's renewed interest in tourism derives from its direct and indirect roles in reducing poverty and achieving the United Nations millennium development goals. Tourism is currently estimated to contribute around 10 percent of global gross domestic product (GDP) and to be the largest contributor to employment worldwide. Thus tourism can impact positively on local economic development (LED) and, in turn, can lead to poverty reduction in destination communities and countries.